BCG as a Case Study for Precision Vaccine Development: Lessons From Vaccine Heterogeneity, Trained Immunity, and Immune Ontogeny - Angelidou, Asimenia; Diray-Arce, Joann; Conti, Maria Giulia; Smolen, Kinga K.; van Haren, Simon Daniël; Dowling, David J.; Husson, Robert N.; Levy, Ofer (Frontiers in Microbiology, 2020)
Vaccines have been traditionally developed with the presumption that they exert identical immunogenicity regardless of target population and that they provide protection solely against their target pathogen. However, it is increasingly appreciated that vaccines can have off-target effects and that vaccine immunogenicity can vary substantially with demographic factors such as age and sex. Bacille Calmette-Guérin (BCG), the live attenuated Mycobacterium bovis vaccine against tuberculosis (TB), represents a key example of these concepts. BCG vaccines are manufactured under different conditions across the globe generating divergent formulations. Epidemiologic studies have linked early life immunization with certain BCG formulations to an unanticipated reduction (~50%) in all-cause mortality, especially in low birthweight males, greatly exceeding that attributable to TB prevention. This mortality benefit has been related to prevention of sepsis and respiratory infections suggesting that BCG induces “heterologous” protection against unrelated pathogens. Proposed mechanisms for heterologous protection include vaccine-induced immunometabolic shifts, epigenetic reprogramming of innate cell populations, and modulation of hematopoietic stem cell progenitors resulting in altered responses to subsequent stimuli, a phenomenon termed “trained immunity”. In addition to genetic differences, licensed BCG formulations differ markedly in content of viable mycobacteria key for innate immune activation, potentially contributing to differences in the ability of these diverse formulations to induce TB-specific and heterologous protection. BCG immunomodulatory properties have also sparked interest in its potential use to prevent or alleviate autoimmune and inflammatory diseases, including type 1 diabetes mellitus and multiple sclerosis. BCG can also serve as a model: nanoparticle vaccine formulations incorporating Toll-like receptor 8 agonists can mimic some of BCG’s innate immune activation, suggesting that aspects of BCG’s effects can be induced with non-replicating stimuli. Overall, BCG represents a paradigm for precision vaccinology, lessons from which will help inform next generation vaccines.